1990
DOI: 10.1093/nar/18.10.2909
|View full text |Cite
|
Sign up to set email alerts
|

Activationin vitroof RNA polymerase II and III directed transcription by baculovirus produced E1A protein

Abstract: The baculovirus expression system has been successfully used to overproduce a number of different protein products. In this report we describe the construction of a recombinant baculovirus containing the adenovirus E1A 13s cDNA sequence. Infection of insect cells with this virus results in the production of phosphorylated E1A protein. The phosphorylation pattern appears to be similar to the complex pattern associated with E1A protein synthesis in mammalian cells. Purified baculovirus generated E1A protein acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…Previous studies on the effects of viral infection on RNA pol III transcription have documented increases in the activity of the general pol III transcription factor TFIIIC. Notably, the adenovirus E1A protein has been shown to stimulate both the transcriptional activity and DNA binding activity of TFIIIC (8,17,25,29,30,37,60). Similarly, both the herpes simplex virus immediate-early protein ICP27 and the human immunodeficiency virus Tat protein have been reported to increase TFIIIC transcriptional activity (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effects of viral infection on RNA pol III transcription have documented increases in the activity of the general pol III transcription factor TFIIIC. Notably, the adenovirus E1A protein has been shown to stimulate both the transcriptional activity and DNA binding activity of TFIIIC (8,17,25,29,30,37,60). Similarly, both the herpes simplex virus immediate-early protein ICP27 and the human immunodeficiency virus Tat protein have been reported to increase TFIIIC transcriptional activity (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…This system was likely to be advantageous over a prokaryotic expression system because many proteins produced in this manner arc soluble and the insect cells can carry out certain eukaryotic post-translational modifications such as phosphorylation (Miyamoto et al 1985;Olio and iMamatis 1987). In addition, several reports demonstrate that recombinant transcriptional regulators produced by this system are active in vitro (Patel and Jones 1990;Watson and Hay 1990). cDNA cloning studies of both mouse and human p50 have suggested that it is primarily synthesized as a larger precursor protein, pi05, and may be matured by proteolytic removal of its carboxyl region.…”
Section: Nf-kb Subunits P50 and P65mentioning
confidence: 99%
“…Owing to this large genome size it is not possible to insert foreign DNA by conventional techniques such as the use of restriction endonuclease cleavage sites. The method used therefore, relies upon homologous recombination between viral DNA and an appropriate transfer vector when cotransfected into insect cells (5)(6)(7)(8)(9). The transfer vector consists of the recombinant gene inserted downstream of the polyhedrin promoter flanked by the same sequences that flank the polyhedrin gene in the intact virus.…”
Section: Introductionmentioning
confidence: 99%